Comparisonal analysis of profitability and leverage of hotel, restaurant and tourism sub sector companies before and during covid-19 pandemic - Nurul Rizki Yanti; Agrianti Komalasari; Kiagus Andi (Lighthouse Publishing, 2022)
The worldwide economy, particularly Indonesia's, has been negatively impacted by the COVID-19 pandemic. Some of the industries most impacted by the COVID-19 epidemic are those in the hotel, restaurant, and tourism industries. This study uses profitability and leverage to examine whether there are differences in the profitability and leverage situations before and after the COVID-19 epidemic. There are discrepancies between the findings of earlier studies, who found no differences between profitability before and during the COVID-19 epidemic. In this research, a comparative descriptive methodology and a quantitative technique were applied. From 2018 through 2022, financial statistics are used in this analysis. Purposive sampling was used to collect samples, and 25 companies that match the criteria were found. When data were not normally distributed, the non-parametric Wilcoxon signed rank test was employed instead of the paired sample t-test as the normality test. The study's conclusion demonstrates the leverage and profitability of businesses in the travel, dining, and hospitality sectors both before and after the COVID-19 epidemic. In the 25 organizations that were analyzed, the results revealed a significant value (α) of 5% and a decline in the value of profitability and leverage. This indicates that the Indonesian hotel, restaurant, and tourism sub-sector businesses have suffered as a result of the COVID-19 outbreak. This study's findings are anticipated to be used to investment decision-making. Additionally, this research can be used as information by businesses facing profitability and leverage issues before and during the pandemic so that they can take immediate action to maintain their operations going forward.